Speech-language idiopathic disorder prevalence in children from one to eleven years of age - Andrade, Claudia Regina Furquim de (Revista de Saúde Pública, 1997)
OBJECTIVE: The study of the epidemiological aspect of speech-language idiopathic disorders. The profile relates to the prevalence rate among children from 1 to 11 years old. METHOD: The subjects were assessed with regard to speech, language and myofunctional oral aspects. After diagnosis, the subjects were classified according to their principal disorder. Then the disorders were placed in separate age groups. The prevalence rates were applied. RESULTS: The sample for this study included 2,980 children, 125 with primary communicative disorders (prevalence rate = 4.19). The highest general prevalence related to the 3 to 8 year old age-group. The critical phase was that from 4 to 5 years of age. The most prevalent idiopathic speech-language disorders were: articulatory disorders; then oral language delays and miofunctional and neurovegetative disturbances. DISCUSSION: It is important to note that the communication disorder prevalence rate is very significant during childhood. It is a serious problem in Brazil, because although we have more critical cases there are no national preventive programs for these pathologies. It is, therefore, expected that this problem will increase rapidly in the near future if there isn't governmental action.